The Box for Early Detection of Gas Leaks and Fires uses Notification System to The Fire Department - Saparuddin Saparuddin; Muhammad Amin; Sudarmin Sudarmin (Forum Kerjasama Pendidikan Tinggi, 2022)
Fire is one of the tragedies that cannot be predicted, besides being unwanted by the community, fires are also often uncontrolled when the fire has started to grow. Fire incidents are very dangerous and disrupt people's lives. Many types of fire detection devices have developed recently to minimize the occurrence of material losses and fatalities that provide a sense of security for the users of these detectors, but there are still some things that need to be added to this detector in order to reduce the number of material losses and victims. soul, the researcher wants to design a tool with a working system when the fire sensor detects the fire value and the gas sensor detects the gas value, the sensor sends data to the NodeMCU. Furthermore, NodeMCU will send a message in the form of a notification in the form of the complete address of the owner of the house where the fire occurred as input into the program sketch. A notification is sent to the Tanjungbalai City Fire Department operator and the buzzer will turn on and the LED will light up